Evaluation of LL-37 antimicrobial peptide derivatives alone and in combination with vancomycin against S. aureus. (November 2018) - Shurko, James; Galega, Ralph; Li, Chuxi; Lee, Grace
Abstract Treatment ofStaphylococcus aureus infections continues to be a challenge due to antimicrobial resistance. Endogenous antimicrobial peptides may offer a new option for treatingS. aureus infections but several factors limit their clinical utility. Herein, we studied the activity of the antimicrobial peptide LL-37 and two truncated derivatives, LL-13 and LL-17 alone and in combination with vancomycin against a range of drug-resistantS. aureus strains including methicillin resistantS. aureus (MRSA) and vancomycin resistantS. aureus (VRSA) strains in vitro. When used with vancomycin, LL-13 and LL-17 displayed synergy against VRSA and showed the ability to restore sensitivity to vancomycin after pretreatment. In addition, LL-13 and LL-17 showed a strong ability to inhibitS. aureus biofilm production. LL-37 derivatives may be useful in treating infections that are resistant to vancomycin or in scenarios where biofilm formation is a concern.